2018
DOI: 10.1155/2018/5315098
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of Dementia in Patients with Antidepressants: A Meta-Analysis of Observational Studies

Abstract: Antidepressants are the most commonly and widely used medication for its effectiveness in the treatment of anxiety and depression. A few epidemiological studies have documented that antidepressant is associated with increased risk of dementia so far. Here, our aim is to assess the association between antidepressant use and risk of dementia in elderly patients. We searched articles through MEDLINE, EMBASE, Google, and Google Scholar from inception to December 1, 2017, that reported on the association between an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 26 publications
1
56
0
5
Order By: Relevance
“…Regarding the potential effects of antidepressant medication, although not significant after accounting for multiple comparisons, those prescribed 'any antidepressant' appeared to be at a higher risk of developing dementia in our cohort. This is in line with the growing evidence for this association from observational studies, 32 and is consistent with a large, matched, prospective cohort study that found that antidepressant monotherapy was associated with an over twofold increased dementia risk in those aged over 60 after adjusting for multiple confounders, including depression. 33 Poor antidepressant response has been reported to be indicative of an especially increased risk of dementia in patients with cognitive impairment, 34 and it is likely that a number of patients in our study were referred to secondary care following treatment failure because over half had been prescribed antidepressants prior to reaching the service.…”
Section: Open Accesssupporting
confidence: 89%
“…Regarding the potential effects of antidepressant medication, although not significant after accounting for multiple comparisons, those prescribed 'any antidepressant' appeared to be at a higher risk of developing dementia in our cohort. This is in line with the growing evidence for this association from observational studies, 32 and is consistent with a large, matched, prospective cohort study that found that antidepressant monotherapy was associated with an over twofold increased dementia risk in those aged over 60 after adjusting for multiple confounders, including depression. 33 Poor antidepressant response has been reported to be indicative of an especially increased risk of dementia in patients with cognitive impairment, 34 and it is likely that a number of patients in our study were referred to secondary care following treatment failure because over half had been prescribed antidepressants prior to reaching the service.…”
Section: Open Accesssupporting
confidence: 89%
“…Approximately 46.8 million people worldwide were afflicted with dementia in 2015, and this number is expected to reach 131.5 million by 2050 [2]. Several studies suggested that oxidative stress, senile plaques, vascular impairment, cerebrovascular atherosclerosis, β-amyloid, neurofibrillary tangles, and hyperphosphorylated tau protein accumulation could be responsible for developing dementia [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Para Wang et al (2018), a tecnologia da informação, com base nos sistemas de informação em saúde, tem ganhado bastante evidência nos últimos anos, particularmente por oportunizar a redução de erros clínicos, como erros de medicação, erros de diagnóstico e para apoiar os profissionais de saúde oferecendo informações atualizadas. Eles prometem melhorar fluxo de trabalho e a eficiência dos cuidados, aumentando, assim, a qualidade geral de cuidados de saúde.…”
Section: Resultsunclassified
“…Com relação aos desafios na adoção da tecnologia da informação, Wang et al (2018) afirmam que a área da saúde tem sido particularmente lenta e atrasada em comparação com outras áreas. Isso é devido à complexidade em questões como interoperabilidade, racionalidade tecnológica, aceitabilidade, racionalidade gerencial, segurança de dados e qualidade dos dados.…”
Section: Resultsunclassified